FASILITAS PENGOLAHAN SAMPAH TERPADU EDUKATIF KELURAHAN SUNGAI LULUT KOTA BANJARMASIN - Nur Isnania Hanifa; Yuswinda Febrita (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
The waste management issue in Banjarmasin City, particularly in Sungai Lulut Village, is driven by limited processing facilities and low community participation. The Integrated Waste Processing Facility is designed as both a processing area and an educational center using an interactive approach and recycled materials. The spatial layout is organized based on Bloom’s taxonomy, incorporating stages of information, observation, interaction, and creation. Recycled materials function not only as construction elements but also as visual and physical learning media. The integration of educational and processing functions within one site creates a spatial system that supports improving community understanding of waste management at its source.